1999
DOI: 10.1017/s002531549700012x
|View full text |Cite
|
Sign up to set email alerts
|

On reproduction and age of the squid Loligo vulgaris from the Saharan Bank (north-west African coast)

Abstract: Loligo vulgaris (Cephalopoda: Loliginidae) is a commercially important species in the cephalopod trawl fishery in the Saharan Bank (21–26°N). This study on squid in central-east Atlantic waters aims to examine some important aspects of its reproductive biology. In the period from May 1993 to April 1994 monthly samples of L. vulgaris were collected from this commercial trawl fishery. The maturation pattern for males and females was described from the proportion of immature, maturing and mature animals in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 19 publications
5
28
1
5
Order By: Relevance
“…Sexual dimorphism in size is well known in loliginids, and males of many species show larger maximum sizes than females (Moreno et al, 1994;Raya et al, 1999;Rocha and Guerra, 1999;Perez et al, 2002). This was clearly seen in the present study for both Loligo species.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Sexual dimorphism in size is well known in loliginids, and males of many species show larger maximum sizes than females (Moreno et al, 1994;Raya et al, 1999;Rocha and Guerra, 1999;Perez et al, 2002). This was clearly seen in the present study for both Loligo species.…”
Section: Discussionsupporting
confidence: 77%
“…Appropriate standard indices of maturity and reproductive activity were tested before adopting the gonadosomatic index (GSI) (sensu Macy, 1982;Raya et al, 1999;Perez et al, 2002), which is defined here as:…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the age and growth of L. vulgaris from statolith analysis have estimated the duration of their post-hatching life to be about 1 yr, i.e. 240 to 396 d (Natsukari & Komine 1992, Arkhipkin 1995, Bettencourt et al 1996, Raya et al 1999, Rocha & Guerra 1999. Statolith analysis has proved to be the best tool for estimating loliginid age and growth of wild populations, with nearly all studies focusing on analysis of the post-hatching area of the statolith (see the reviews Jackson 1994 andO'Dor 2001).…”
Section: Introductionmentioning
confidence: 99%
“…the East Atlantic and the Mediterranean Sea. Statolith collections from previously published studies on L. vulgaris age and growth (Arkhipkin 1995, Raya et al 1999, Rocha & Guerra 1999 were analyzed, as well as newly collected material. From these aged statoliths it was possible to estimate by back-calculation the respective hatching dates and the sea temperature ranges recorded for each geographic region at hatching.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on loliginids reported that size-at-maturity in squid can vary dramatically, depending on the location and time of collection of samples (Raya et al, 1999;Perez et al, 2002;Rodrigues and Gasalla, 2008). The size-at-maturity of squid caught by the shrimp trawling off the coast of São Paulo and Santa Catarina, was relatively smaller than the ones found in SSI by the present study.…”
Section: Discussionmentioning
confidence: 99%